(untitled) (American International Journal of Economics and Finance Research, 2021)
As the Sultanate of Oman in the process of uses e-services among public services by adopting of technological implication in the services of the government in recent time. Therefore, it is a timely initiative to develop a conceptual framework between the e- service, digital transformations attributes and efficiency of the digital transformation, Oman. In order to development of conceptual model study examined review of literature on about the effectiveness of electronic services and digital transformation in the selected public sector in the Sultanate of Oman. The study used online empirical sources in the names of organizational, technology, environment and human resource factors, as well as the effectiveness of digital change in various online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald Full text, Scopus and EBSCO HOST, etc. The study review results show that organizational, technological, environmental and human factors play an important role in ensuring the effectiveness of the public sector in the digital transformation in the Sultanate of Oman. The study also found that there is mediating role of E-service in the relationship between digital transformations attributes and the digital transformation. Based on the summary of literature review, the study provides guidance for the future scope of empirical research and develop a conceptual framework between the e- service, digital transformations attributes and efficiency of the digital transformation to conduct a rigorous study in Oman and its regions.